Factors affecting on green entrepreneurial success (evidence from the entrepreneurs in western province of sri lanka) - Sivashanker, R. (University of Jaffna, 2022)
Purpose: Concept of the green entrepreneur culture has become vital in the context of contemporary society. The study is constructed as to identify the influence of individual, social and institutional factors in green entrepreneurial culture and its growth. The critical success factor or factors that are significant in inculcating the growth of green entrepreneurship can be explored for the future development in this field. Methodology: The study is a descriptive analysis comprising the western province as the sample of the study. Being the business performance is the dependent variable there are major driving factors comprising individual, societal and institutional factors. Each factor comprised the sub element of five variables that are influencing directly or indirectly towards the green entrepreneurial success as per the literature review and the empirical evidences. The schools of entrepreneurial traits and green theory have underpinned the analysis of the study. The two hundred and fifty registered SMEs in the western province used for the study via cluster representative sample using through primary data collection method. Chi-square test, confirmatory factor analysis have been used to validate the hypothesis and the results to associate with the literature. Findings: Though the individual, social and institutional factors are weighing on the green movements of entrepreneurial success the individual factors have proven as the most influential elements which affect the destructive green entrepreneurs. The study addresses that the individual factors are contributing in creating more successful ventures in fact the personal efficacy in creating uniqueness and bench mark for being as the green entrepreneurs. On the other hand the absence of green funds, absence of instant gain, green cost and degree of competition and the application of innovative technologies are the real challenges faced by the entrepreneurs to sustain as green entrepreneurs . Research limitations: the study has been considered the samples only from the western province and it might cause the issues in generalizing the findings in common. Also the concept of green entrepreneurship and its culture are still emerging therefore there are some other factors to be considered apart from the literature. Implications: The intimation on personal traits and the expectations of economical concerns are significantly involved in green venture growth. The social factors and institutional factors are influencing not only to the initiation but also to the successive growth of the ventures and the green culture.
Keywords: Green entrepreneurship; Personal traits; Green ventures; Green ideologies